Corporate governance and securities class actions. (November 2014) - Chapple, Larelle; Clout, Victoria J; Tan, David
This study investigates the governance attributes of firms that have been subject to securities class actions (SCAs). There has been a recent sizable increase in the number of firms subject to SCAs in Australia. We examine a sample of firms that have been subject to SCAs due to disclosure breaches and match the firms by industry and size to a control sample. First, we examine the compliance culture of the SCA firms via the frequency of Australian Securities Exchange (ASX) queries of the firm and find that the frequency of ASX queries is positively associated with the occurrence of a SCA. Secondly, we provide evidence that SCA firms exhibit weaker levels of corporate governance than the matched control sample. In addition, we contribute to the understanding of firms subject to SCAs and their corporate governance attributes. Our results suggest the presence of a nomination committee may be associated with higher agency costs and that the influence of CEO duality may reduce the effectiveness of a nomination committee.